Fitness consequences of early life conditions and maternal size effects in a freshwater top predator. (19th February 2016) - Vindenes, Yngvild; Langangen, Øystein; Winfield, Ian J.; Vøllestad, Leif Asbjørn
Summary: Conditions experienced in early life stages can be an important determinant of individual life histories. In fish, environmental conditions are known to affect early survival and growth, but recent studies have also emphasized maternal effects mediated by size or age. However, the relative sensitivity of the mean fitness (population growth rate λ) to different early life impacts remains largely unexplored. Using a female‐based integral projection model (IPM) parameterized from unique long‐term demographic data for pike ( Esox lucius ), we evaluated the relative fitness consequences of different early life impacts, including (i) maternal effects of length on egg weight, potentially affecting offspring (first year) survival, and (ii) effects of temperature on offspring growth and survival. Of the seven vital rates defining the model, offspring survival could not be directly estimated and four scenarios were defined for this rate. Elasticity analyses of the IPM were performed to calculate (i) the total contribution from different lengths to the elasticity of λ to the projection kernel, and (ii) the elasticity of λ to underlying variables of female current length, female offspring length at age 1, and temperature. These elasticities were decomposed into contributions from different vital rates across length. Egg weight increased with female length, as expected, but the effect leveled off for the largest females. However, λ was largely insensitive to this effect, even when egg weight was assumed to have a strong effect on offspring survival. In contrast, λ was sensitive to early temperature conditions through growth and survival. Among mature females, the total elasticity of λ to the projection kernel generally increased with length. The results were robust to a wide range of assumptions. These results suggest that environmental conditions experienced in early life represent a more important driver of mean population growth and fitness of pike than maternal effects of size on offspring survival. We discuss two general mechanisms underlying the weak influence of this maternal effect, suggesting that these may be general for long‐lived and highly fecund fishes. This model and results are relevant for the management of long‐lived top predators, including many commercially important fish species. Abstract : Environmental conditions experienced in early life represent a more important driver of mean population growth and fitness of pike than maternal effects of body size on offspring survival. These results are derived using an integral projection model estimated with unique long‐term demographic data from Windermere, United Kingdom.